(3eONd eYGUQ HESJNOGe GdMGSH GdCdjs - (3CMeO MSjf(B, (3Ydj MSjfs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2002)
(3jJfGhd gPG GdcJGH aj WjGJg JMdjd GdbQGQ CSGdjH GdHQeLI GdNWjI hGdYOOjI hGdCgOGa heLehYI ef feGPL GdJMdjds
(3cJGH eeRbs
Keywords: (3GdMGSH GdBdjs; (3GdeMGSHIs